2021
DOI: 10.1002/ange.202100091
|View full text |Cite
|
Sign up to set email alerts
|

Steric Hindrance in Metal Coordination Drives the Separation of Pyridine Regioisomers Using Rhodium(II)‐Based Metal–Organic Polyhedra

Abstract: The physicochemical similarity of isomers makes their chemical separation through conventional techniques energy intensive.H erein, we report that, instead of using traditional encapsulation-driven processes,s teric hindrance in metal coordination on the outer surface of Rh II -based metalorganic polyhedra (Rh-MOPs) can be used to separate pyridine-based regioisomers via liquid-liquid extraction. Through molecular dynamics simulations and wet experiments,w ed iscovered that the capacity of pyridines to coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, molecules can be separated according to their capacity to coordinate to Rh( ii )-based MOPs, which is influenced by the basicity and steric hindrance of their constituent coordinating heteroatoms. 61 This approach could prove highly valuable for diverse applications, including currently low-yielding catalytic reactions that are limited by solubility restraints of the reagents and/or catalysts. Thus, we believe that further refinement of this coordinative solubilising methodology will enable researchers to surpass the solubility constraints in homogeneous organic chemistry.…”
Section: Post-synthetic Modification Of Metal–organic Polyhedramentioning
confidence: 99%
“…Therefore, molecules can be separated according to their capacity to coordinate to Rh( ii )-based MOPs, which is influenced by the basicity and steric hindrance of their constituent coordinating heteroatoms. 61 This approach could prove highly valuable for diverse applications, including currently low-yielding catalytic reactions that are limited by solubility restraints of the reagents and/or catalysts. Thus, we believe that further refinement of this coordinative solubilising methodology will enable researchers to surpass the solubility constraints in homogeneous organic chemistry.…”
Section: Post-synthetic Modification Of Metal–organic Polyhedramentioning
confidence: 99%
“…Previous studies have shown that cuboctahedral rhodium-based MOPs (Rh-MOPs), which are assembled from 1,3-benzenedicarboxylate and dirhodium paddlewheels, offer very interesting possibilities for separation processes. The cavity of Rh-MOPs can be used for selective entrapment of gases/molecules, whereas their reactive surface can be used to coordinatively attach selected molecules . The chemical robustness of Rh-MOPs enables them to sustain their performance even when exposed to harsh conditions, such as exposure to water, acids, or competing coordinating ligands .…”
Section: Introductionmentioning
confidence: 99%
“…The cavity of Rh-MOPs can be used for selective entrapment of gases/molecules, 12 whereas their reactive surface can be used to coordinatively attach selected molecules. 13 The chemical robustness of Rh-MOPs enables them to sustain their performance even when exposed to harsh conditions, such as exposure to water, acids, or competing coordinating ligands. 14 In addition, the surface of Rh-MOPs can be functionalized to modulate their solubility from water to polar/non-polar organic solvents, which increases their processability and enables using them under homogeneous conditions or shaping them into functional macroscopic objects.…”
Section: Introductionmentioning
confidence: 99%